2021
DOI: 10.1186/s12885-021-07797-6
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of lower glucose consumption for IDH1 mutated gliomas on FDG-PET

Abstract: Background Non-invasive diagnosis of IDH1 mutation for gliomas has great clinical significance, and PET has natural advantage to detect metabolism, as IDH mutated gliomas share lower glucose consumption. Methods Clinical data of patients with gliomas and 18F-FDG PET were retrospectively reviewed. Receiver operating characteristic curve (ROC) analysis was conducted, and standard uptake value (SUV) was estimated in combination with grades or IDH1 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…On the other hand, glucose metabolism as assessed by FDG PET in IDH -wildtype tumors tended to be higher than that in IDH -mutant tumors in the present study, but the difference did not reach statistical significance. This result was not in agreement with previous studies, in which the FDG uptake of IDH -wildtype tumors was significantly higher than that of IDH -mutant tumors [ 13 15 ]. This could be because the previous studies included all grades of diffuse gliomas (WHO grade II–IV), but the present study examined FDG PET only in malignant tumors (WHO grade III and IV).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, glucose metabolism as assessed by FDG PET in IDH -wildtype tumors tended to be higher than that in IDH -mutant tumors in the present study, but the difference did not reach statistical significance. This result was not in agreement with previous studies, in which the FDG uptake of IDH -wildtype tumors was significantly higher than that of IDH -mutant tumors [ 13 15 ]. This could be because the previous studies included all grades of diffuse gliomas (WHO grade II–IV), but the present study examined FDG PET only in malignant tumors (WHO grade III and IV).…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study showed that IDH -mutant cells shift glucose metabolism from glycolysis to the TCA cycle [ 11 , 12 ]. In addition, several clinical studies demonstrated that the glucose uptake of IDH -mutant gliomas was significantly lower than that of IDH -wildtype gliomas [ 13 15 ]. Recently, an exploratory study using oxygen-sensitive molecular MRI revealed that IDH -mutant gliomas exhibit lower hypoxia and acidity compared with IDH -wildtype gliomas [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also show that IDH1-derived 2hydroxyglutarate can facilitate degradation of Hif1-α and thus reduce the Warburg-effect through down-regulation of multiple genes in the glycolytic pathway (113). Further evidence of an inhibitory effect of the IDH1 mutation on glucose consumption and glycolysis was obtained recently from PET analysis (116). The long-term survival of the patient could therefore result in part from a synergistic interaction between his self-directed KMT and the anti-cancer effects of the IDH1-R132H mutation.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to results observed for murine CT-2A glioma, recrystallized CHCA matrix in positive polarity mode was enriched for metabolites in pathways grouped as Carbohydrate Metabolism rather than Energy Metabolism. This is likely a reflection of the biology of decreased glucose uptake in IDH -mutant tumors compared to IDH -wildtype tumors, such as CT-2A glioma [26].…”
Section: Resultsmentioning
confidence: 99%